2011
DOI: 10.1039/c1ob05268c
|View full text |Cite
|
Sign up to set email alerts
|

Rapid carbonylative coupling reactions using palladium(i) dimers: applications to 11CO-radiolabelling for the synthesis of PET tracers

Abstract: Palladium dimers with sterically hindered phosphines have been shown to be excellent pre-catalysts for the aminocarbonylation of aryl halides to yield amides and one of them has been successfully employed as a pre-catalyst for the synthesis of 11C-radiolabelled amides for PET imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…We previously reported a copper(I)‐tris(3,5‐dimethylpyrazolyl)borate (CuTp*) solution that enabled quantitative [ 11 C]CO trapping and its subsequent use in palladium(0)‐mediated carbonylation of benzylamine and aryl iodides to produce [ 11 C]amides . During these experiments, it was observed that replacing the palladium(0) catalyst with a palladium(II) species led to the formation of [ 11 C]dibenzylurea as a major side product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported a copper(I)‐tris(3,5‐dimethylpyrazolyl)borate (CuTp*) solution that enabled quantitative [ 11 C]CO trapping and its subsequent use in palladium(0)‐mediated carbonylation of benzylamine and aryl iodides to produce [ 11 C]amides . During these experiments, it was observed that replacing the palladium(0) catalyst with a palladium(II) species led to the formation of [ 11 C]dibenzylurea as a major side product.…”
Section: Resultsmentioning
confidence: 99%
“…That the Pd(PPh 3 ) 2 Cl 2 system produces comparable yields in the absence of free triphenylphosphine indicates that the latter species may not be required for the release of [ 11 C]CO from the copper(I) complex. Indeed, aminocarbonylation reactions have previously been performed using CuTp*[ 11 C]CO solutions in the absence of such a displacing ligand …”
Section: Resultsmentioning
confidence: 99%
“…Substrates screened by using the developed microfluidic method. , we decided to use the same mol % of the compound since, as we have shown recently, [31] the second Pd in the dimer is likely to be a "sacrificial" palladium and is not involved in the catalysis.…”
Section: A C H T U N G T R E N N U N G (M-i) 2 a C H T U N G T R E N mentioning
confidence: 96%
“…Recently we have shown for the first time that Pd dimer precatalysts of the type [Pd 2 A C H T U N G T R E N N U N G (m-I) 2 A C H T U N G T R E N N U N G (PtBu 3 ) 2 ] are highly active for performing carbonylation reactions in short reaction times. [31] We have now used this pre-catalyst in combination with our segmented flow microfluidic reactor to screen a small number of substrates for carbonylation reactions. One of the key challenges when performing carbonylation reactions with this type of catalyst is ensuring the addition of reagents in a specified order.…”
mentioning
confidence: 99%
“…Complex 123 (Cu(Tp*)) was later used in a series of Pd‐mediated 11 C‐carbonylations to synthesize simple 11 C‐labeled amides, carboxylic acids, and ureas . Furthermore, it was possible to prepare [ 11 C ]MK‐0233 ( 124 ), a PET tracer for the neuropeptide Y Y5 receptor using this methodology (Scheme ) …”
Section: Carbonylation Using [11c ]Comentioning
confidence: 99%